The Relationship Between Community Compliance with the Use of Masks in Preventing Covid-19 - Salwa, Manna; Mutia, Rika (Benih : Journal of Midwifery, 2022)
In the midst of the COVID-19 pandemic, individual attitudes towards prevention measures play a crucial role in curbing the transmission of the virus. This study explores the relationship between attitudes towards COVID-19 prevention and the accuracy of information dissemination, focusing on online news data analysis. COVID-19, caused by the RNA virus SARS-CoV-2, poses significant health risks globally. Data collection involved gathering datasets from various online news websites. Utilizing a system that analyzes text data, the study achieved a remarkable accuracy rate of 95% in processing 10 news stories. The key factor influencing this accuracy level is the alignment of words in the testing data with the training data stored in the system database. The findings underscore the importance of individual attitudes in shaping preventive behaviors and highlight the critical role of accurate information dissemination in combating the COVID-19 pandemic.